Optimum Combination of Insulin-Transferrin-Selenium and Fetal Bovine Serum for Culture of Rabbit Articular Chondrocytes in Three-Dimensional Alginate Scaffolds - Lanlan Zhang; Hong Song; Xiaojun Zhao (International Journal of Cell Biology)
Fetal bovine serum (FBS) has been reported to affect chondrocyte biosynthesis in monolayer culture. Insulin-Transferrin-Selenium (ITS) was investigated as a partial replacement for FBS during in vitro culture of rabbit articular chondrocytes in three-dimensional alginate scaffold. Chondrocyte-seeded alginate hydrogels were cultured in Dulbecco's modified Eagle's medium plus 10% FBS, 1% ITS plus 2% FBS, 1% ITS plus 4% FBS, or 1% ITS plus 8% FBS. At designed time point, the Chondrocyte-seeded alginate hydrogels were harvested and evaluated with histological staining, immunohistochemistry, and quantitative gene expression analysis. Viable cell density and cell division were also evaluated. Chondrocytes biosynthesis and cell division in 1% ITS with 2% FBS medium were similar to that in medium added with 10% FBS. For a total culture of 3 weeks, phenotypic gene expression in chondrocyte-seeded hydrogels was maintained at high levels in medium with 1% ITS plus 2% FBS, while it was decreased to varying degrees in the other groups. In conclusion, with 1% ITS, medium with 2% FBS could promote chondrocyte biosynthesis and cell division, and prevented cell dedifferentiation in three-dimensional alginate scaffolds.